2023
DOI: 10.1111/nmo.14539
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of olorinab, a full agonist of the cannabinoid receptor 2, for the treatment of abdominal pain in patients with irritable bowel syndrome: Results from a phase 2b randomized placebo‐controlled trial (CAPTIVATE)

Abstract: Background: Olorinab is a highly selective, peripherally acting, full agonist of cannabinoid receptor 2. This study assessed the efficacy and safety of olorinab to treat abdominal pain in patients with irritable bowel syndrome with diarrhea (IBS-D) and constipation (IBS-C).Methods: CAPTIVATE was a phase 2b, randomized, double-blind, placebo-controlled, parallel-group trial. Eligible participants aged 18-70 years with IBS-C and IBS-D diagnosed per Rome IV received olorinab 10 mg, 25 mg, or 50 mg three times dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…Cannabinoids impact GI function through CB receptors, TRPV1, and glycine channels, but their effects can vary depending on the location of these receptors. 117,118 Knowing the location of these receptors might be needed in delineating the mechanisms of adverse effects as well as the beneficial effects of cannabinoids. Because of its effects on GI motor and secretory functions and centrally mediated effects on visceral hypersensitivity, cannabis have been used in a variety of chronic GI disorders, such as gastroparesis, IBS and IBD, and functional dyspepsia, but results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoids impact GI function through CB receptors, TRPV1, and glycine channels, but their effects can vary depending on the location of these receptors. 117,118 Knowing the location of these receptors might be needed in delineating the mechanisms of adverse effects as well as the beneficial effects of cannabinoids. Because of its effects on GI motor and secretory functions and centrally mediated effects on visceral hypersensitivity, cannabis have been used in a variety of chronic GI disorders, such as gastroparesis, IBS and IBD, and functional dyspepsia, but results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids impact GI function through CB receptors, TRPV1, and glycine channels, but their effects can vary depending on the location of these receptors 117,118 . Knowing the location of these receptors might be needed in delineating the mechanisms of adverse effects as well as the beneficial effects of cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabidiol chewing gum was ineffective in the treatment of perceived pain in irritable bowel syndrome [37]. However, a meta-analysis by Doeve et al [38] revealed an alleviating effect on patient-reported symptoms and increased quality of life scores after cannabinoids and phase 2b randomized placebo-controlled trial (CAPTIVATE) showed the significant impact of olorinab (an agonist of cannabinoid receptor 2) on abdominal pain (moderate to severe) reduction [39]. Similarly, inhaled cannabis did not affect pain in the randomized clinical trial of patients with sickle cell disease [40].…”
Section: Medical Cannabis and Cannabinoidsmentioning
confidence: 99%
“…This compound reduced pain response measures in a rat osteoarthritis model (Han et al, 2017) and in mouse and rat models of inflammatory bowel disease (Castro et al, 2022). In two Phase 2 trials, APD371 improved abdominal pain associated with Crohn's disease for specific patient subgroups, and the compound was found to be well tolerated (Chang et al, 2021; Yacyshyn et al, 2021).…”
Section: In Vivo Disease Models To Clinical Trialsmentioning
confidence: 99%